Gap Analysis Towards Service Quality in McDonald's Dago - Naraswari, Ni Putu Radha; Fachira, Ira (Journal of Business and Management, 2015)
Abstract. The raising numbers of fast food restaurants nowadays are the result of the increasing demand for relatively inexpensive, and ready-to-eat food. This condition makes the competition among fast food restaurant is getting bigger. To deal with the high competition in fast food market, McDonald’s Dago as one of the fast food restaurant in Bandung should provide the best service to make customer satisfied. By measuring the service quality, McDonald’s Dago will be able to know whether the service that has been provided satisfies its customers or not. The purpose of this research is to measure the service quality by using the SERVQUAL method. There are five dimensions in SERVQUAL method, which are tangible dimension, reliability dimension, responsiveness dimension, empathy dimension, and assurance dimension. In this research, the service quality of McDonald’s Dago will be measured by calculating the differences between customers’ expectation and customers’ perception. This difference is called customer gap. From the customer gap result, it is possible to know which SERVQUAL dimension that customers’ feel satisfied from service that provided by McDonald’s Dago. The data collection in this research will be from primary data, which is questionnaire. There are 22 statements in the questionnaire that are from SERVQUAL model, and the questionnaire will be spread to 100 respondents of ITB Undergraduate students. The data analysis shows that all of the customer gaps are negative, which means the service that has been provided by McDonald’s Dago did not meet customers’ expectation. Keywords: Service quality, SERVQUAL, Customer Gaps, Customer Perception, Customer Expectation, Restaurant industry